The Sustainable Implementation of Ecosystem‑Based Adaptation to Climate Change in Coastal Area: Lessons from Indonesia - Wen, Yafang; Tian, Youyue; Kato, Naomi; Ray, Anuska; Ariyaningsih; Shaw, Rajib (Prevention and Treatment of Natural Disasters, 2025)
Climate change has signiϐicantly impacted coastal areas of developing Asian countries, causing rising sea levels, frequent extreme weather events, and ecosystem degradation. In recent years, ecosystem‑based adaptation (EbA) policies have played a vital role in addressing climate change and bringing many beneϐits to local residents by establishing a sustainable green economy. This study ϐinds that although Ecosystem‑based Adaptation (EbA) projects have been widely implemented in coastal areas of Indonesia, their effectiveness and sustainability still need improvement. The long‑term success of these projects depends on the cooperation mechanisms among the government, communities, and implementing organizations, with the enforcement of EbA policies being particularly crucial. Additionally, funding shortages or inadequate ϐinancial oversight are common challenges EbA projects face worldwide. At the project level, issues such as ϐlawed design and insufϐicient community participation hinder sustainability. More importantly, coastal ecosystems are not static; they evolve throughout the project’s implementation, potentially leading to outcomes that deviate from expectations or cause negative impacts. Based on these factors, this study categorizes the key factors affecting the sustainability of EbA projects into four dimensions: policy and governance, ϐinance, socio‑economic aspects, and ecological environment. In response to these challenges, several policy recommendations are proposed, including promoting community participation, attracting high‑level talent, establishing economic incentive mechanisms, securing long‑term ϐinancial support, and integrating indigenous knowledge into project design. This study not only analyses the sustainability challenges of coastal EbA projects but also provides practical guidance and future directions for EbA implementation and research.